Draft genome sequence of halomonas elongata MH25661 isolated from a saline creek in the andes of Peru - Ilucion Mamani J. (2019)
Halomonas elongata strain MH25661, a moderate halophile, was isolated from a saline creek in the Andes of Peru. Genome annotation analyses revealed genes that respond to osmotic stress and oxidative stress, genes that are involved in sporulation, and genes that are involved in transport systems and resistance to antibiotics and toxic compounds. Copyright © 2019 Mamani et al.